Synthesis and reactivity of cyclometalated triamidophosphine complexes of niobium and tantalum - Sietzen, Malte; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2015)
The triamidophosphine protioligand 1 reacts with the homoleptic pentakis(dimethylamido) precursors of niobium and tantalum [M(NMe2)5, where M = Nb, Ta] to form cyclometalated complexes of the type [N2PCN-κ5-N,N,P,C,N]M(NMe2) (2-M). Apart from the three amido donors, one benzylic position of the ligand backbone is deprotonated over the course of this reaction, resulting in the formation of a new M-C bond. As a consequence, a metallaziridine substructure is formed, and the triamidophosphine moiety thus serves as a tetraanionic pentadentate ligand. The dimethylamido complexes 2-M can be converted into the corresponding triflates [N2PCN-κ5-N,N,P,C,N]M(OTf) (3-M) and alkyl complexes [N2PCN-κ5-N,N,P,C,N]M(CH2SiMe3) (4-M) by treatment with triethylsilyl triflate (Et3SiO3SCF3) followed by (trimethylsilyl)methyllithium (LiCH2SiMe3). The alkyl complexes exhibit interesting reactivities, including a second cyclometalative backbone activation affording the trimethylphosphine-stabilized complexes [NP(CN)2-κ6-N,P,C,N,C,N]M(PMe3) (5-M). In the case of tantalum, the formation of a dinuclear hydrido complex (6) is observed upon hydrogenation of 4-Ta. In the case of niobium, the metallaziridine substructure in 4-Nb is prone to ring opening via protonation with triphenylsilylamine (Ph3SiNH2), resulting in formation of the corresponding imido complex [PN3-κ4-P,N,N,N]Nb═NSiPh3 (7).